Correlation between pronated foot posture, movement quality and postural stability among college students: a pilot study - Krishna, Harish S.; Kudi, Sreejisha Puthu; Kanchinadka, Anupa (International Journal of Research in Medical Sciences, 2025)
Background: Postural control and movement mechanics are significantly influenced by foot position. Pronated foot posture has been associated with reduced movement quality and impaired balance. It is characterized by medial arch collapse and foot eversion. College students may be more prone to these musculoskeletal abnormalities as a result of their lifestyle choices and extended periods of inactivity. Methods: The 22 college students between the ages of 18 and 25 participated in a pilot cross-sectional study. The Flamingo balance test (FBT) was used to test static balance, the Y-balance test (YBT) was used to measure dynamic balance, the foot posture index-6 (FPI-6) was used to measure foot posture, and the functional movement screen (FMS) was used to evaluate movement quality. The association between postural stability, movement quality, and pronated foot posture was ascertained using Pearson's correlation coefficient. Results: FPI-6 showed a strong negative correlation with FMS (r=-0.72, p<0.001 right; r=-0.599, p=0.003 left) and static balance (r=-0.75, p<0.001 right; r=-0.55, p=0.008 left). No significant correlation was observed with dynamic balance (p>0.05). FMS was positively correlated with static balance (r=0.648, p=0.001 right; r=0.621, p=0.002 left) but not with dynamic balance (p>0.05). Conclusions: The study found that college students who have pronated foot posture have considerably worse static and dynamic balance as well as lower movement quality. Early detection and foot posture-focused remedial measures may enhance functional results and avert further musculoskeletal problems.